Protecting Digital Society: Policies for Criminalizing Illegal Smartphone Applications Through Cyber Law Frameworks - Tokan, Kity; Amin, Muhammad Erham; Syaufi, Ahmad; Mispansyah , Mispansyah (West Science Law and Human Rights, 2024)
This research aims to contribute to the development of criminal law policies addressing the widespread distribution of smartphone applications, both APK and iOS, that are used as tools for unauthorized online loan activities, online fraud, threats, and intimidation. These applications often disguise themselves as legitimate online loan platforms, wedding invitation apps, and parcel delivery services. Upon download, they illicitly debit mobile banking accounts or present themselves as government auction platforms for criminal goods at discounted prices, posing significant threats to consumers, debtors, and the general public. Theoretical framework: The foundation of this research lies in cyber law theory, which endeavors to create legal strategies to address cybercrimes and safeguard the digital community. This study utilizes a multidisciplinary approach, integrating legal analysis, policy assessment, and collaboration with stakeholders. Methods: This study utilized the normative juridical method to examine digital policies by criminalizing illegal smartphone applications through cyber law policies. This approach involves a systematic legal analysis of current regulations, assessing their effectiveness, and suggesting formal legal measures to address new threats posed by unauthorized applications, with an emphasis on protecting digital society from harm. Results and Conclusions: This indicates a pressing need for comprehensive criminal law policies specifically designed to effectively combat these unauthorized applications. Such policies are crucial in preventing and mitigating the harms caused by these applications before they impact society. The author's contribution lies in proposing formal offenses against the creators and disseminators of these applications. malicious applications, thereby bridging the current gap in legal measures to counteract digital criminal activities. Originality/Value: This research underscores the urgency of formulating and implementing cyber law policies to safeguard the public from the detrimental effects of illicit smartphone applications. Its originality lies in proposing innovative legal strategies to proactively address emerging digital threats.